Hydrogen uptake induced by CO2 enhances hydrogen embrittlement of iron in hydrogen blended natural gas. (October 2022) - Zhou, Chengshuang; He, Yanmin; Jiang, Jiehao; Zhang, Kaiyu; Tang, Dan; Zhu, Haohao; Shang, Juan; Sun, Guomin; Wang, Meng; Zhang, Lin; Wu, Min; Zheng, Jinyang
Abstract: The hydrogen embrittlement behaviour of pure iron in different environments is investigated via fatigue crack growth tests, hydrogen permeation tests and first-principles calculations. The results show that the fatigue crack growth rate (FCGR) in H2 is much higher than that in N2 . NG and CO2 further enhanced FCGR in an H2 environment. Hydrogen permeation tests show that both CO2 and NG can accelerate the diffusion of hydrogen in pure iron. This is mainly because CO2 can effectively reduce the diffusion activation energy of hydrogen atoms from the surface of pure iron to the subsurface. Highlights: Natural gas and CO2 promote fatigue crack growth of iron in the H2 environment. Natural gas and CO2 reduce hydrogen penetration time in pure iron. Natural gas and CO2 don't increase the steady-state current of hydrogen permeation. CO2 is a key factor in natural gas to promote hydrogen embrittlement. CO2 reduces the energy barrier for H diffusing from the surface to the subsurface.